The Essential Features of the Criminal Offence A Comparative Study The Republic of Moldova and Romania: Array - Pasat, Aurel Octavian (Acta Universitatis Danubius. Juridica, 2021)
The importance of criminal law is given by the urgent need to defend the essential values ​​of the society on which it is based. Within these values a decisive place is occupied by the man regarded as the supreme social value; he must benefit from criminal protection in all its attributes: life, bodily integrity, health, physical and mental liberty, sexual inviolability, dignity, inviolability of home and correspondence. All the acts, actions or inactions which violate all the values ​​mentioned above through their content are called criminal offences. According to what is presented further, we will carry out a comparative study between the legislation of the Republic of Moldova and that of Romania, regarding the essential features of the criminal offence as they are listed and described in the legislations of both countries. We express our opinion concerning the four essential features of the criminal offence: social danger, illegality, guilt, liability for criminal punishment.